TYPOGRAPHY AND CULTURE: INDIAN SCRIPTS AS VISUAL AND ARTISTIC HERITAGE - Kumari, Sapna; Gautam, Sachiv; Yadav, Rahul; Kumar Yadav, Kishan; Vardhan Singh, Abhishek (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The research paper describes how Indian scripts are not merely utilized to write and communicate but they were also a significant element in our culture, and art. Writing in India has been related to religion, traditions and creativity. Language and spirituality have a strong connection since the origin of drawing and symbols to the correct scripts. Examples of such scripts include Brahmi, Devanagari, Tamil and Bengali which evolved over a long period of years. Their forms and designs are determined by the location, the materials, and culture at the particular moment. Each of the scripts appears to be different and symbolizes the identity of a specific area. The paper further demonstrates how in the past writing was regarded as something sacred. Individuals thought that letter writing was a religious and disciplined action. These scriptures have design guidelines such as balance, rhythm and flow and hence are beautiful in addition to being easy to read. Letters are not words only, but also appear to be works of art. The traditional styles began to become lost with the printing and digital technology. However, modern amenities are also assisting designers to revive those old styles in new forms. The Indian scripts are applied today in design and advertisement as an expression of culture and feelings. In general, the Indian scripts continue to evolve over time that continues to be of great cultural importance.